Regards and Views toward International Accounting Standards Setting: A Critical Examination and Discussion - Ahmad, Afzal (Asian Business Review, 2015)
Accounting information is the basis for the stakeholders who take different economic decision time to time by assessing those accounting information reported by the business organization. That’s why; international accounting standard setting committee aims to protect the interest of the stakeholders by formulating a high-quality reporting standard. But this standard setting process is hindered by many external lobbying groups like government, political, economic and corporate group because there are the agency and other problems. This study aims to examine and discuss the theoretical and conceptual frameworks like different approaches and theories like a free market and regulatory approach. Moreover, it is still a debate whether free market or regulatory approach ensures the interest of the stakeholders more. However, this study identifies that standard setting process should be a holistic approach that should protect the interest of not only the stakeholders but also the organization.
Keywords: IAS; Accounting Information; Stakeholders; Marketing System Quality; Standard Setting Process; Holistic Approach